1994
DOI: 10.1111/j.1476-5381.1994.tb13202.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of cyclic AMP‐induced Cl conductance in aqueous humour formation by the dog ciliary epithelium

Abstract: 1 The effects of isoprenaline, a forskolin derivative NKH-477, and dibutyryl cyclic AMP (db cyclic AMP) on the membrane potential, conductance and cell volume of the dog non-pigmented ciliary epithelium (NPE) were investigated by intracellular potential recording, nystatin-perforated patch clamp technique and videomicroscopic cytometry. 2 The resting membrane potential of NPE was about -70 mV in physiological saline and was depolarized by isoprenaline in a dose-dependent manner with an EDm of about 3 nM. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…A membrane-permeant form of cAMP, 8-BrcAMP, was reported to depolarize porcine ciliary epithelium by ϳ10 mV (23). That action could reflect activation of Cl Ϫ channels of either the NPE (10,11,20) or of PE cells (24). Consistent with the observation in transformed cultured cells (24), we have now documented that 8-Br-cAMP activates Cl Ϫ channels of native bovine PE cells, facilitating Cl Ϫ release and thereby reducing the cell volume.…”
Section: Discussionsupporting
confidence: 60%
“…A membrane-permeant form of cAMP, 8-BrcAMP, was reported to depolarize porcine ciliary epithelium by ϳ10 mV (23). That action could reflect activation of Cl Ϫ channels of either the NPE (10,11,20) or of PE cells (24). Consistent with the observation in transformed cultured cells (24), we have now documented that 8-Br-cAMP activates Cl Ϫ channels of native bovine PE cells, facilitating Cl Ϫ release and thereby reducing the cell volume.…”
Section: Discussionsupporting
confidence: 60%
“…8 In isolated dog NPE cells, forskolin and cAMP induce a Cl Ϫ current along with a concomitant decrease in cell volume. 9 These findings suggest that stimulation of cAMP formation facilitates ion transport to the posterior chamber, resulting in an increased rate of formation of aqueous humor. On the contrary, it has been demonstrated that topical isoproterenol decreases the formation of aqueous humor and IOP in human.…”
mentioning
confidence: 91%
“…( MacLeod et al 1994, Lang et al 1998, it has also been reported that Cl K conductance operated by cAMP and PKA is activated by the addition of forskolin in some cell types, such as rat cardiomyocytes and dog ciliary epithelium (Chen et al 1994, Tilly et al 1996. What is intriguing about our results is that the cAMP pathway that activates ion channels in sperm does not appear to involve PKA to any major extent: at 5 mmol/l the PKA inhibitor H-89 had little effect on isotonic volume, whereas similar concentrations of Bis I and lavendustin increased it markedly (Table 2).…”
Section: Pkc-and Camp-dependent Pathwaysmentioning
confidence: 99%